ANALYSIS OF SPATIAL AND TEMPORAL PRICE EFFICIENCY OF COWPEA (Vigna unguiculata [L] Walp) IN SELECTED LOCAL GOVERNMENT AREAS OF GOMBE STATE, NIGERIA - Lamarana, B.L.; Danwanka, H. A.; Mohammed, S.Y.; Hamidu, K.; Abubakar, D. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study analysed spatial and temporal price efficiency of cowpea (Vigna unguiculata [L.] Walp) in selected Local Government Areas of Gombe State, Nigeria. A multi-stage sampling technique was employed in selecting 130 cowpea merchants based on number of cowpea merchants in each market. Data were obtained from both primary and secondary sources. Secondary data were obtained on monthly average retail prices per 100kg bag of Cowpea for the period (2012 – 2019) from Bureau of Statistics, Gombe State. Data collected were analysed using spatial and temporal price models and net seasonal rise in price. The result revealed the existence of both positive and negative inter market price differential. The highest and lowest price spread for Billiri were recorded in June, 2015 (₦11,360) and February, 2018 (-₦13,700), whereas for Yamaltu Deba they were recorded in July, 2018 (₦18,400) and July, 2012 (-₦12,400), respectively. This could be due to inadequate information on prices and supply in the various markets, inefficient transportation system and other physical facilities. The highest percentage net seasonal increase in Gombe, Billiri and Yamaltu Deba were recorded in August 2012 (136.98), September 2012 (102.23) and July 2012 (160.54) respectively. It could be concluded that the pricing system of cowpea marketing in the study area was inefficient. The study recommends the establishment of adequate market infrastructures including physical buildings, road networks and storage facilities. Policy aimed at making the food distribution system efficient should be implemented. Large and sustained investment by stakeholders in cowpea marketing is also recommended so as to make cowpea production and marketing a focal business away from its present subsistence state. This can be achieved through provision of low interest loan to marketers for processing and storage activities.